2012
DOI: 10.1373/clinchem.2011.169094
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Angiogenic Markers for the Early Diagnosis and Prediction of Preeclampsia

Abstract: BACKGROUND An imbalance in circulating factors that regulate blood vessel formation and health, referred to as angiogenic factors, plays a central role in the pathogenesis of preeclampsia. CONTENT Several studies have demonstrated a strong association between altered circulating angiogenic factors and preeclampsia. These factors include circulating antiangiogenic proteins such as soluble fms-like tyrosine kinase 1 and soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 91 publications
2
60
0
6
Order By: Relevance
“…Considerable effort has been made to identify biomarkers that could predict women who will develop preeclampsia [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Although markers of systemic inflammation [79,80] and endothelial dysfunction [81][82][83][84][85][86][87][88] in maternal blood have been associated with preeclampsia, their prognostic performance for the identification of patients with preeclampsia prior to diagnosis has been disappointing [79][80][81]83,[89][90][91].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable effort has been made to identify biomarkers that could predict women who will develop preeclampsia [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Although markers of systemic inflammation [79,80] and endothelial dysfunction [81][82][83][84][85][86][87][88] in maternal blood have been associated with preeclampsia, their prognostic performance for the identification of patients with preeclampsia prior to diagnosis has been disappointing [79][80][81]83,[89][90][91].…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia [63][64][65][66][67]69,70,72,[92][93][94][95][96][97][98][99][100][101][102][103], as well as other obstetrical syndromes [46,[104][105][106][107][108][109][110][111][112][113][114][115][116][117][118], is characterized by an anti-angiogenic state. Plasma concentrations of the angiogenic factor, placental growth factor (PlGF), are decreased [69,70,92,93,96,[100][101][102], and the anti-angiogenic factors (soluble vascular endothelial growth factor receptor-1 [sVEGFR-1] and soluble endoglin [sEng]) are elevated both prior to [67,72,[119]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early termination of pregnancy is one of the main treatments for the patients with severe preeclampsia (Haddad et al 2010). The efficient diagnosis and prediction method for preeclampsia is still unavailable (Hagmann et al 2012). The high efficient and safe way for precise diagnosis of preeclampsia is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the relationship of first trimester PAPP-A to serial levels of placental growth factor (PlGF) and serial ratios of sFlt-1 to PlGF were also explored, as studies have shown that PlGF is significantly lower in preeclampsia [9] and the ratio of sFlt-1/PlGF is also significantly elevated in preeclampsia [10,11], prior to the onset of clinical signs.…”
Section: Introductionmentioning
confidence: 99%